United States Air Force Physician Assistant Postgraduate Specialty Training Factors: A Brief Survey. Issue 4 (December 2018) - Rabener, Michael J.; Bonjour, Timothy J.
Abstract : Purpose: The purpose of this study was to determine USAF physician assistants' (PAs') concerns regarding postgraduate education and training. Methods: This was a single-mode, observational, cross-sectional study using an anonymous-structured survey involving a population of 420 active duty USAF PAs. Potential participants were contacted by email and asked to take a one-time survey via a secure survey site link. Results: One hundred ten USAF PAs participated in the survey seeking their opinions on factors affecting applying for military postgraduate specialty training. The prime factors identified fell into 3 major groups of concern: types of degrees offered, current job satisfaction, and types of specialty training available. The most desired degree and specialty options were the doctorate of science and emergency medicine. Only a small number of respondents (6%) expressed current job satisfaction and the desire to remain in family medicine. Conclusions: This study revealed important information to senior leaders who fund, recruit, train, and maintain force-readiness requirements. The 3 identified main priorities of respondents were the types of degrees, current level of job satisfaction, and the types of specialty training. The vast majority of those surveyed preferred the doctorate, which is what all of the specialty degrees in the Air Force are, except for ENT.